Distributed sliding mode control for leader‐follower formation flight of fixed‐wing unmanned aerial vehicles subject to velocity constraints - Wang, Xiangke; Yu, Yangguang; Li, Zhongkui (International journal of robust and nonlinear control, 2021)
Summary This paper considers the leader‐follower formation flight of fixed‐wing unmanned aerial vehicles (UAVs) subject to velocity constraints. A novel distributed sliding mode control law is proposed for each UAV, whose kinematics is described by a unicycle model with a saturated angular velocity and a bounded linear velocity within an interval. The designed control law of each follower UAV only uses its own information and the information of its leader UAV. Driven by the designed control law, the desired formation is achieved with rigorous proof, while the follower UAVs' constraints of both the linear and angular velocities are satisfied. Moreover, the follower's speed adjustment range is relaxed and not required to be strictly larger than their leaders'. Finally, numerical simulations are presented to verify the results.